# Revision history [back]

### group algebra

Can anyone help in writing a code to find the list of idempotent and primitive elements of a group algebra, the examples goes like this. Let p be an odd prime such that $\bar2$ generates $U(Z_{p^2})$ and G=(ideal generated by a)∗ (ideal generated by b) an abelian group, with $o(a)=p^2$ and $o(b)=p$. Then $F_2G$ has four inequivalent minimal codes, namely, the ones generated by the idempotents $e_0= \hat{G}$, $e_1=\hat{b}−\hat{(ideal generated by 'a')∗ (ideal generated by 'b')}$(note: its a big hat), $e_2=\hat{a−G}$ and $e_3=\hat{(ideal generated by 'a_p')∗ (ideal generated by 'b')}−\hat{G}$. 2 None

### group algebra

Can anyone help in writing a code to find the list of idempotent and primitive elements of a group algebra, the algebra?

The examples goes like this. Let p $p$ be an odd prime such that $\bar2$ generates $U(Z_{p^2})$ and G=(ideal let $G =(\text{ideal generated by a)∗ (ideal }a) ∗ (\text{ideal generated by b) }b)$ an abelian group, with $o(a)=p^2$ and $o(b)=p$. $o(b)=p$.

Then $F_2G$ has four inequivalent minimal codes, namely, the ones generated by the idempotents $e_0= \hat{G}$, $e_1=\hat{b}−\hat{(ideal idempotents: $$e_0 = \hat{G}$$ $$e_1=\hat{b}−\widehat{(\text{ideal generated by 'a')∗ (ideal }a)∗ (\text{ideal generated by 'b')}(note: its a big hat), e_2=\hat{a−G} and e_3=\hat{(ideal }b)}$$ $$e_2=\widehat{a−G}$$ $$e_3=\widehat{(\text{ideal generated by 'a_p')∗ (ideal }a_p)∗ (\text{ideal generated by 'b')}−\hat{G}.}b)}−\hat{G}$$ 3 retagged FrédéricC 4383 ●3 ●37 ●93 ### group algebra Can anyone help in writing code to find the list of idempotent and primitive elements of a group algebra? The examples goes like this. Let$p$be an odd prime such that$\bar2$generates$U(Z_{p^2})$and let$G =(\text{ideal generated by }a) ∗ (\text{ideal generated by }b)$an abelian group, with$o(a)=p^2$and$o(b)=p$. Then$F_2G\$ has four inequivalent minimal codes, namely, the ones generated by the idempotents:

$$e_0 = \hat{G}$$ $$e_1=\hat{b}−\widehat{(\text{ideal generated by }a)∗ (\text{ideal generated by }b)}$$ $$e_2=\widehat{a−G}$$ $$e_3=\widehat{(\text{ideal generated by }a_p)∗ (\text{ideal generated by }b)}−\hat{G}$$